2021
DOI: 10.1186/s42238-021-00093-x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis for pain: a cross-sectional survey of the patient information quality on the Internet

Abstract: Background Cannabis has increasingly become an alternative treatment for chronic pain, however, there is evidence of concomitant negative health effects with its long-term usage. Patients contemplating cannabis use for pain relief commonly see information online but may not be able to identify trustworthy and accurate sources, therefore, it is imperative that healthcare practitioners play a role in assisting them in discerning the quality of information. The present study assesses the quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…While it would be desirable that news outlets and commercial websites provided more complete information, our findings suggest that health professionals should point their patients toward websites from non-profit organizations or health portals to get more comprehensive information and allow them to make informed decisions. It is reassuring, in this respect, that our study shows that the ranking provided by Google gives higher visibility to health portals and non-profit organizations, in agreement with the findings by Ng et al for websites on medical cannabis and chronic pain (Ng et al, 2021). The number of webpages mentioning medical cannabis in the context of specific indications not aligned with regulatory approval might indicate both where public health authorities should focus their strategies to disseminate information and, potentially, where a clear answer from clinical trials or systematic reviews are needed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While it would be desirable that news outlets and commercial websites provided more complete information, our findings suggest that health professionals should point their patients toward websites from non-profit organizations or health portals to get more comprehensive information and allow them to make informed decisions. It is reassuring, in this respect, that our study shows that the ranking provided by Google gives higher visibility to health portals and non-profit organizations, in agreement with the findings by Ng et al for websites on medical cannabis and chronic pain (Ng et al, 2021). The number of webpages mentioning medical cannabis in the context of specific indications not aligned with regulatory approval might indicate both where public health authorities should focus their strategies to disseminate information and, potentially, where a clear answer from clinical trials or systematic reviews are needed.…”
Section: Discussionsupporting
confidence: 92%
“…(Jia et al, 2021 ) A study by Jia et al found that 24% of the webpages returned by Google (and 59% of YouTube videos) had a positive stance on the use of medical cannabis in glaucoma (Jia et al, 2021 ). Ng et al (Ng et al, 2021 ), although not specifically investigating the stance of the websites, have shown that they often were of low quality according to standard measures of information quality and that quality was higher for health portals and lower for commercial websites.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study to broadly evaluate the quality of health information provided by online cannabis vendors selling to Canadian consumers, with no restrictions on health conditions or purpose of use. Ng et al recently used the DISCERN instrument to evaluate the quality of web-based consumer health information at the intersection of cannabis and pain [ 34 ]. Although the averaged DISCERN scores were found to be higher than those in our study, the quality of health information in this area was still concluded to be poor.…”
Section: Discussionmentioning
confidence: 99%
“…Web pages categorized as peer-reviewed (ie, peer-reviewed journal articles) were not included in the accuracy analysis, as peer-reviewed literature was used to create the evidence-based summary used in the content assessment. This approach has been used by others conducting similar content analyses [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among studies that specifically looked at cannabis health claims on the internet, one found only 5% of claims on the health benefits of cannabis aligned with evidence [ 20 ]. Other studies reported that web-based information about cannabis use for pain was biased as sources often neglected to discuss potential risks [ 21 ] or were just unreliable [ 22 ]. This points to variable quality of cannabis-related information available on the internet [ 20 , 23 - 26 ].…”
Section: Introductionmentioning
confidence: 99%